Site-specific incidence of ring-related injuries in Rufous Fantails Rhipidura rufifrons. Issue 1 (2nd January 2018) - Nietmann, Lindsey; Ha, Renee R.
ABSTRACT: Although colour-ringing is generally considered safe, a small proportion of avian species experience significant ring-related injuries. We report the first description of ring-related injuries in a rhipidurid flycatcher, the Rufous Fantail, and show that, in a population on Rota in the Northern Mariana Islands, switching from plastic to metal rings reduced but did not eliminate ring-related injuries. Over 30% of Rufous Fantails experienced severe injuries (tarsal swelling and leg loss) while wearing plastic rings and 11.7% experienced injuries while wearing metal rings. Injuries were not caused by improper fit of the rings and the use of metal rings in a separate population in Iluka, Australia, did not appear to cause any injuries. We suggest that injuries are caused by the accumulation of spider silk around the tarsus. Rufous Fantails may be more susceptible to injuries on Rota than in Iluka due to the frequency with which they encounter spider webs. We recommend avoiding the use of plastic rings on rhipidurids and related species and, more specifically, developing alternative marking schemes for the potential reintroduction of Rufous Fantails to Guam, where spider webs are abnormally abundant.